2016
DOI: 10.1097/pcc.0000000000000765
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Anticonvulsant Selection and Electroencephalographic Monitoring Following Severe Traumatic Brain Injury in Children—Understanding Resource Availability in Sites Participating in a Comparative Effectiveness Study

Abstract: Objective Early post-traumatic seizures (PTS) may contribute to worsened outcomes after traumatic brain injury (TBI). Evidence to guide the evaluation and management of early PTS in children is limited. We undertook a survey of current practices of continuous electroencephalographic monitoring (cEEG), seizure prophylaxis and the management of early PTS to provide essential information for trial design and the development of PTS management pathways. Design Surveys were sent to site principal investigators at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…That manuscript reported that 40% of North American and 42% of European centers state that they routinely provide EEG monitoring for children with severe TBI. (10) Children in our study with known risk factors for PTS(6, 26, 3133) including young age, abusive injury mechanism, and SDH, were more likely to receive EEG monitoring. Young children and those who suffered child abuse tended to receive EEG monitoring earlier in the hospitalization.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…That manuscript reported that 40% of North American and 42% of European centers state that they routinely provide EEG monitoring for children with severe TBI. (10) Children in our study with known risk factors for PTS(6, 26, 3133) including young age, abusive injury mechanism, and SDH, were more likely to receive EEG monitoring. Young children and those who suffered child abuse tended to receive EEG monitoring earlier in the hospitalization.…”
Section: Discussionmentioning
confidence: 74%
“…(10) Overall, 16.5% of all patients received NMB after day 0 (NMB use on day 0 is more likely be procedure-related and temporary). Those patients received a median of 2.0 (1.0, 3.0) days of NMB beyond day 0.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations